Meningkatkan perilaku hidup bersih dan sehat (PHBS) anak usia 4-5 tahun melalui metode bercerita - Pangestuti Pangestuti (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Clean and Healthy Living Behavior (PHBS) in early childhood is a learning program to introduce and instill the principles of clean and healthy living from an early age. This study aims to prepare children to form new habitual behaviors by familiarizing themselves with clean and healthy daily living behaviors from an early age in order to implement health protocols so that children avoid the risk of transmission of various diseases including Covid-19. To teach PHBS to early childhood, teachers use the storytelling method, which is a method used by teachers to provide teaching experiences for children through oral. This type of research is Classroom Action Research (CAR) with a qualitative research approach. The time of this research was carried out in August 2021. The subjects of this study were 10 group A children of TK ABA Bendan and all of them were 4-5 years old. The object of this research is clean and healthy living behavior (PHBS). Data collection techniques were carried out by observation (observation), interviews, and documentation. The data analysis technique in this study uses qualitative data analysis, from the data that has been collected or collected it will be analyzed using qualitative and quantitative descriptive techniques with percentages. Based on the results in the observations, it was found that there was an increase in the clean and healthy living behavior (PHBS) of children aged 4-6 years through the storytelling method which can be seen from the number of percentages with the criteria for developing well. In the initial conditions before the action of 0% in the first cycle increased to 50% and in the second cycle to 80%. The impact of developing PHBS with the storytelling method is that children will imitate the activity so that they gain experience about a learning activity from what they see, hear, and experience about an event.